Inflammation in the posterior elements, in particular the facet joint and facet joint ankylosis over 2-year follow-up in radiographic axial spondyloarthritis - de Hooge, Manouk (2024)
Publisher Copyright: © Author(s) (or their employer(s)) 2024. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.